Cicatricial Ectropion Correction in the Inferior Eyelid with Cartilaginous Tissue Graft: Case Report (International Journal of Medical and Surgical Sciences, 2014)
Transcutaneous approaches of the lower eyelid are commonly used to provide adequate exposure of the orbital floor and zygomaticomaxillary suture during treatment of facial fractures. Cicatricial ectropion is a rare complication that results in a shortened eyelid. This condition can be temporary in some cases but when it is permanent it must be surgically corrected, aiming to restore function, improve the aesthetical outcomes and to prevent ophthalmological disorders such as epiphora and corneal ulceration. The present study describes a novel surgical approach, associated with a concomitant cartilaginous graft, to treat severe lower eyelid ectropion resultant from a previously performed subtarsal incision.